Methods Of Basic Argument, Discussion, Question And Answer And Dialogue According To The Quran - Saripudin Saripudin; Dudung Ali Nurdin; Yayan Yayan; Titin Karlina; Mastuhi Mastuhi (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this research is to elaborate on the basic methods of arguing, discussion, debriefing, and dialogue in the Qur'an as important methods in Islamic education. The research method used was library research; data were collected through observation and documentation and analyzed based on qualitative analysis. The results of the study show that the values of Islamic education are found in Surah Al-Anbiya verses 51–56: that Allah has provided very clear instructions for humanity and that humans need to be careful in using human potential, especially the eyes, ears, and heart/mind. In the context of gaining knowledge, it must be used as much as possible, in addition to the obligation to fulfill scientific mandates. The knowledge obtained is not a suggestion of arrogance but a means of doing good deeds. The values of Islamic education in the story of Prophet Ibrahim, as found in Surah Al-Anbiyâ verses 51-72, include: (1) Aqidah values; (2) Ukhuwah/hablunminannas values; and (3) Tawhid values.The morals demonstrated in Prophet Ibrahim's story are noble morals, both in dealing with his disbelieving father and his infidel people.(3) The educational value of thinking and discussing, as Prophet Ibrahim AS did in conveying the truth and correcting the mistakes of his people in worship by means of dialogue using logic and not in a selfish and fanatical way, (4) The value of education is gentle and argumentative, without violence. Prophet Ibrahim put forward da'wah arguments to invite his father and people to the truth.